My Math Forum induction
 User Name Remember Me? Password

 Algebra Pre-Algebra and Basic Algebra Math Forum

 September 19th, 2016, 10:02 AM #1 Member   Joined: May 2016 From: Ireland Posts: 96 Thanks: 1 induction prove by induction for all positive integers n: 1+5+9+13+........+(4n-3)= n/2(4n-2) i tried this by trying to prove n/2(4n-2)+ (4(k+1)-3) = k+1/2(4(k+1)-2) but it did not work out for me.
 September 19th, 2016, 10:16 AM #2 Senior Member   Joined: Dec 2012 From: Hong Kong Posts: 853 Thanks: 311 Math Focus: Stochastic processes, statistical inference, data mining, computational linguistics You mean the second step of the induction? Assume $\displaystyle 1 + 5 + 9 + ... + (4k-3) = \frac{k(4k-2)}{2}$. Then $\displaystyle 1 + 5 + 9 + ... + (4k-3) + [4(k+1)-3] = \frac{k(4k-2)}{2} + 4(k+1)-3 = \frac{k(4k-2) + 8(k+1) - 6}{2} = \frac{4k^2-2k + 8k+8 - 6}{2} = \frac{4k^2+6k+2}{2}=\frac{(k+1)(4k+2)}{2}=\frac{(k +1)(4(k+1)-2)}{2}$.
 September 19th, 2016, 10:51 AM #3 Senior Member   Joined: Aug 2016 From: morocco Posts: 273 Thanks: 32 For the second step, you must say: let k be an integer >=1 such that 1+5+...(4k-3)=.... (IH) let's prove that 1+5+....(4k--3)+(4(k+1)-3)=...... then we use the induction hypothesis.

 Tags induction

 Thread Tools Display Modes Linear Mode

 Similar Threads Thread Thread Starter Forum Replies Last Post med1student Algebra 10 September 4th, 2015 08:09 PM Tommy_Gun Algebra 14 June 1st, 2012 11:52 PM TheTree Algebra 1 May 28th, 2012 10:54 AM gaussrelatz Algebra 4 September 28th, 2011 08:55 PM Tommy_Gun Number Theory 0 December 31st, 1969 04:00 PM

 Contact - Home - Forums - Cryptocurrency Forum - Top

Copyright © 2018 My Math Forum. All rights reserved.